Meningkatkan Pengetahuan dan Keterampilan Guru dalam Menyusun RPP K13 Sederhana Darurat Covid melalui Metode “Tamu Datang“ di Sekolah Binaan pada Tahun 2020 - Februartati Februartati (Bedelau: Journal of Education and Learning, 2021)
This study aims to determine whether the "Guest Comes" method can improve the knowledge and skills of teachers in compiling the K13 simplified RPP for the Covid emergency. This research was conducted in two ways, namely face-to-face and online (GUEST COME). Face-to-face is done by means of workshops and observations as well as teacher supervision of the knowledge and abilities of teachers in preparing lesson plans. Observations and supervision carried out by supervisors on teachers in target schools using instruments. while the online method is carried out by supervisors using WA media such as video calls and chats. The results obtained in this study were that prior to the research, the knowledge and skills of teachers in compiling the K13 simplified RPP for COVID-19 emergency was an average of 58.3%. After the research was conducted, there was an increase in the knowledge and skills of teachers in compiling the K13 simplified RPP for the Covid emergency by 85.83%. So it can be said that there has been a significant increase that the use of the "GUEST COME" method can improve the knowledge and skills of teachers in preparing the K13 simplified RPP for the covid emergency.